The Relationship Between Non-Alcoholic Fatty Liver Disease and Metabolic Syndrome in Children - Kokab Namakin; Mahyar Mohammadifard; Mahmoud Zardast; Naemeh Ebrahimabadi (Shiraz University of Medical Sciences, 2017)
Background: With respect to the increased prevalence of fatty liver and its development at young age in the Iranian population, as well as the importance of prevention and control of its related factors, the current study aimed to explore the relationship between fatty liver and metabolic syndrome in 6-18-year-old children in Birjand, Iran. Methods: In this case-control study, thirty 6 - 18-year-old children and adolescents with metabolic syndrome were selected based on Adult Treatment Panel (ATP) III criteria by convenience sampling. Then, 46 children and adolescents not affected by this disease with the same gender and age were selected as the control group. Weight, height, waist circumference, and blood pressure of the participants were measured and recorded, and blood sugar tests, blood lipid profile (triglycerides, cholesterol, high density lipoprotein (HDL) and liver enzymes alanine aminotransferase (SGPT) and aspartate aminotransferase (SGOT) were performed. Data were analyzed by SPSS software using Chi-square test, independent T-test and logistic regression analysis at the significant level of P < 0.05. Results: The mean age in the case and control groups were 13.17 ± 1.64 and 12.46 ± 2.27 years, respectively (P = 0.14). The relative frequency of fatty liver in the case group (86.7%) was higher than that of the control group (28.3%) (P < 0.001), and the chance of developing non-alcoholic fatty liver disease (NAFLD) in patients with metabolic syndrome was 5.38 times greater than healthy people. The results showed a significant relationship between gender, body mass index (BMI) and triglyceride (TG) levels and fatty liver among the participants (P < 0.05). Conclusions: According to the results of the current study, it is recommended to develop some programs to modify the lifestyle and encourage children and adolescents by schools, the media and parents to keep fit.